Investigation of Saturable Absorber Length Effect on Characteristics of Passive Q-Switching and Stokes with Anti-Stokes Pulses Generated in Laser System of Nd:YVO4 - saad, dunya; Abdul-Kareem Mahdi Salih; Asal , Rasool (University of Thi-Qar Journal of Science, 2024)
The effect of the saturable absorbent material on the characteristics of a single laser pulse results from the passive Q-switching method, or two pulses. The first pulse is resulted from the passive Q-switching method and the other is resulted from Stokes pulse generated by the laser ray reaction with the Raman medium in the optical system. This study simulated this effect on the characteristics of three pulses (passive Q-switching pulse, Stokes pulse, and anti-Stokes pulse) simultaneously generated from one optical system . The optical system consists of Nd: YVO4, PbWO4, and Cr + 4: YAG as an effective medium, Raman medium, and saturable absorbent material, respectively. The modeling of the rate equations was used, and the Rung-Kutta-Fehelberg numerical method was used to solve the rate equations. The results show increased power of the pulses generated, requiring an increased length of the saturable absorber material used in the system. The results showed that at the shortest length used for the saturated absorbent material, the pulse duration and energy of the three generated pulses were PQS pulse (16.44ns, 1.39mJ), Stokes pulse (12.59ns, 1.148mJ) and anti-Stokes pulse (13.53ns, 1.59mJ), while at the longest length of the saturated absorbent material, the pulse duration and energy were PQS pulse (14.68ns, 1.50mJ), the Stokes pulse (11.41ns, 1.36mJ) and the anti-Stokes pulse (12.38ns, 1.86mJ).